2018
DOI: 10.1021/acs.jpclett.8b00959
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ligand Promotion of Carbon Dioxide Reduction through Stabilizing Chemisorbed Reactive Intermediates

Abstract: We have explored functionalizing metal catalysts with surface ligands as an approach to facilitate electrochemical carbon dioxide reduction reaction (CORR). To provide a molecular level understanding of the mechanism by which this enhancement occurs, we combine in situ spectroscopy analysis with an interpretation based on quantum mechanics (QM) calculations. We find that a surface ligand can play a critical role in stabilizing the chemisorbed CO, which facilitates CO activation and leads to a 0.3 V decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 32 publications
6
70
0
Order By: Relevance
“…The decreased intensities of signal peaks are likely resultant from the detachment of the non-covalently surface coated porphyrins (either physically adsorbed porphyrins or stacking of the porphyrins via p-p interactions) or blockage of the surface sites by residual electrolytes.F urthermore,t he electrochemically accessible Au surface area of P1-AuNP electrode before and after electrolysis is also similar as evidenced by the comparable peak areas of Au (111) and (110) in the UPD studies ( Supporting Information, Figure S9). Finally,improved durability of the catalytic interface has been confirmed by the consecutive voltammetry study [43] under CO 2 atmosphere,w hich showed that the CV curves nearly coincide after 10 consecutive cycles (Supporting Information, Figure S10).…”
Section: Angewandte Chemiementioning
confidence: 76%
See 1 more Smart Citation
“…The decreased intensities of signal peaks are likely resultant from the detachment of the non-covalently surface coated porphyrins (either physically adsorbed porphyrins or stacking of the porphyrins via p-p interactions) or blockage of the surface sites by residual electrolytes.F urthermore,t he electrochemically accessible Au surface area of P1-AuNP electrode before and after electrolysis is also similar as evidenced by the comparable peak areas of Au (111) and (110) in the UPD studies ( Supporting Information, Figure S9). Finally,improved durability of the catalytic interface has been confirmed by the consecutive voltammetry study [43] under CO 2 atmosphere,w hich showed that the CV curves nearly coincide after 10 consecutive cycles (Supporting Information, Figure S10).…”
Section: Angewandte Chemiementioning
confidence: 76%
“…Both N1sa nd S2p signals are quite consistent with prior features according to the XPS studies (Supporting Information, Figure S8). Finally,improved durability of the catalytic interface has been confirmed by the consecutive voltammetry study [43] under CO 2 atmosphere,w hich showed that the CV curves nearly coincide after 10 consecutive cycles (Supporting Information, Figure S10). Finally,improved durability of the catalytic interface has been confirmed by the consecutive voltammetry study [43] under CO 2 atmosphere,w hich showed that the CV curves nearly coincide after 10 consecutive cycles (Supporting Information, Figure S10).…”
mentioning
confidence: 76%
“…[18][19][20] Recently, the positive role of functional ligands in heterogeneous CO 2 RR electrocatalysis is emerging as a means to modify the reactivity of metallic surfaces. [21][22][23][24][25][26][27][28] Yet, there remains great space to tune the organic component in order to address unanswered questions. In particular, it is unclear the extent to which the functional groups that bind to the metal surface (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the electrochemically accessible Au surface area of P1‐AuNP electrode before and after electrolysis is also similar as evidenced by the comparable peak areas of Au (111) and (110) in the UPD studies (Supporting Information, Figure S9). Finally, improved durability of the catalytic interface has been confirmed by the consecutive voltammetry study under CO 2 atmosphere, which showed that the CV curves nearly coincide after 10 consecutive cycles (Supporting Information, Figure S10).…”
Section: Methodsmentioning
confidence: 79%